Climate, Sustainability, and Future Generations: An Ecotheology for Indonesia’s Ummah of ‘Nonidentity’ - Gade, Anna M. (Studia Islamika, 2025)
The idea of “future generations” is fundamental to discussions of sustainability, climate and “ecotheology.” However, it also poses a philosophical problem of “nonidentity”: i.e., future people do not really exist. Applied issues regarding intergenerational responsibility, risk and justice in climate policy and practice complicate the nonidentity problem beyond the abstract to the realm of the material. Trends in Anglophone philosophy as well as emerging national ecotheology within the Indonesian Ministry of Religious Affairs increasingly view such empirical problems to be grounded in moral and ethical systems. The Qur’anic idea of ummah (community) renders legible what are otherwise intractable problems in climate and sustainability ethics in regard to justice for future “nonidentities,” that is, generations who are yet to face climate danger. With this come wider implications for morality regarding communities that are invisible and erased in human and more-than-human worlds in Southeast Asia and beyond.